2007
DOI: 10.1177/0743558407301914
|View full text |Cite
|
Sign up to set email alerts
|

Youth Civic Engagement in China: Results From a Program Promoting Environmental Activism

Abstract: China is a key player on the global stage, and nearly 300 million Chinese youth stand to be affected by rapid social and ecological transformations. Programs that promote developmental assets in Chinese youth could increase their resilience in the face of contemporary stressors and enhance their capacity to contribute to China's development. In this paper we describe a unique, service-learning approach to youth development, the Jane Goodall Institute's Roots & Shoots program (R&S), as it is implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…People acting as stewards of their environment through community gardening, park management or watershed restoration (Krasny and Tidball, 2009) may contribute to the feeling of self-efficacy in making the environmental conditions more favorable around them. Evidence from climate education programs shows that participants gain in selfefficacy, social competence, and a sense of civic responsibility (Johnson et al, 2007). In turn, a stronger place attachment e the feeling of ownership and responsibility promotes climate-positive behavior, as individuals are more likely to act carefully in a place they value (Gifford, 2008).…”
Section: Social and Individual Coping Capacitiesmentioning
confidence: 98%
“…People acting as stewards of their environment through community gardening, park management or watershed restoration (Krasny and Tidball, 2009) may contribute to the feeling of self-efficacy in making the environmental conditions more favorable around them. Evidence from climate education programs shows that participants gain in selfefficacy, social competence, and a sense of civic responsibility (Johnson et al, 2007). In turn, a stronger place attachment e the feeling of ownership and responsibility promotes climate-positive behavior, as individuals are more likely to act carefully in a place they value (Gifford, 2008).…”
Section: Social and Individual Coping Capacitiesmentioning
confidence: 98%
“…Program activities and meetings were observed and group records and activity reports were reviewed. Detailed contextual information on each country, study methodologies, and results are reported elsewhere (for China; Johnson, et al, 2007;for Tanzania;Johnson-Pynn, & Johnson, 2005a;2005b).…”
Section: Surveysmentioning
confidence: 99%
“…In China, academic pressures, social isolation, economic changes, sociopolitical sensitivities and a new focus on individualism were recurrent themes (Johnson, et al, 2007) In Tanzania, poverty, developmental needs, and health care concerns were thematic (JohnsonPynn, & Johnson, 2005a). Groups interviewed in Tanzania were more likely to be in rural settings, while those in China were more urban.…”
Section: Ecological Factorsmentioning
confidence: 99%
“…Action planning in this context was considered 'to lead to life skills development in planning and organising, decision-making, critical thinking and problem-solving' (ibid, p. 62). Studies of action campaigns were focused at both the school and community level, with environmental projects focusing on issues such as sustainable development in China (Johnson et al, 2007) and India (Gowda et al, 1991).…”
Section: Youth Work Activitiesmentioning
confidence: 99%
“…Studies were also concentrated in the post-2001 publication period, with nearly as many studies conducted in the USA (n=6) as in the Uk (n=5) and one from China. Johnson et al (2007) evaluated 'Roots and Shoots', an environmental action, service learning and youth development programme for young people in China. Taking a 'discovery-orientated' approach, young people, in conjunction with programme coordinators, were asked to organise and take part in three volunteer and service projects that promote animal welfare, the community or the environment.…”
Section: Single Group Designsmentioning
confidence: 99%